Chatbot as a Corporate Communication Tool: Best Practice of a Hungarian HR Services Company - Szőke, Júlia; Lakosy, Dóra (Journal of Ecohumanism, 2024)
The advent of cutting-edge technologies has changed the way humans communicate. Corporate communication also has to face the challenges and take advantage of the opportunities stemming from the evolution of infocommunication technologies. The paper aims to present the best practice of a Hungarian certified company providing full HR services regarding the use of a chatbot software application as a corporate communication tool. The company applies its award-winning chatbot to communicate with its temporary workforce in five different languages. The paper is a single-case study based on secondary and primary research. The empirical research is carried out by means of an in-depth interview with the examined company’s representative to get details about the successful application of the chatbot software. The results reveal that the company was able to successfully integrate a rule-based chatbot into its corporate communications. The use of the chatbot has brought a number of benefits, e.g. time- and cost-effectiveness, satisfaction from both the temporary workforce and the internal staff. The paper concludes that even the most basic type of chatbot software can be applied effectively if the users are informed and well-prepared in advance, meanwhile the knowledge base of the chatbot software is appropriately determined and constantly updated.